Catalyst coating film and preparation method thereof

By adopting a specific proportion of catalyst combination and process processing in the fuel cell, a catalyst coated film with high durability and anti-reverse ability is prepared, which solves the stability of carbon-based support catalysts in harsh environments and achieves high efficiency and long-life operation of the fuel cell.

CN119833659APending Publication Date: 2025-04-15SUZHOU ANJIE TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510055295.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In existing fuel cells, carbon-based support catalysts have poor stability in severe acid-base and potential environments, resulting in corrosion and degradation of the catalyst.

Method used

A catalyst coating film consisting of anode spray slurry and a cathode spray slurry was prepared by mixing different proportions of dispersants and dispersants to prepare a catalyst layer with excellent durability. The catalyst layer consists of Pt/Ti4O7 and IrO2/Ti4O7 as the anode catalyst, and Pt/W-SnO2 and IrO2/W-SnO2 as the cathode catalyst. The stability and activity of the catalyst are improved through specific process parameters and heat treatment conditions.

Benefits of technology

The catalyst-coated film has achieved high durability and anti-reverse ability in high temperature, high humidity, acid and alkali environments, and can effectively resist the situation where the anode is completely undergas and the anode is partially undergas, and extend the service life of the fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833659A_ABST
    Figure CN119833659A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst coating film, and a membrane electrode assembled by adopting the catalyst coating film has very good durability and has dual functions of resisting complete gas shortage of an anode and partial gas shortage of the anode at the same time. The anode spraying slurry is formed by mixing anode slurry and anode anti-antipole slurry, the anode slurry is composed of a dispersing agent and dispersoid, and the dispersoid of the anode slurry is dry resin and an anode catalyst Pt / Ti4O7; the anode anti-antipolar slurry is composed of a dispersing agent and dispersoid, and the dispersoid of the anode anti-antipolar slurry is dry resin and an anode anti-antipolar catalyst IrO2 / Ti4O7; the cathode spraying slurry is composed of cathode slurry and cathode anti-antipole slurry, the cathode slurry is composed of a dispersing agent and dispersoid, and the dispersoid of the cathode slurry is dry resin and a cathode catalyst Pt / W-SnO2; the negative electrode anti-reverse electrode slurry is composed of a dispersing agent and a dispersoid, and the dispersoid of the negative electrode anti-reverse electrode slurry is dry resin and a negative electrode anti-reverse electrode catalyst IrO2 / W-SnO2; dispersing agents of all the slurry are ultrapure water and isopropanol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, in particular to a catalyst coating membrane. The present invention also provides a method for preparing the catalyst coating membrane. Background Art

[0002] Fuel cells have the advantages of high efficiency, environmental protection, and quiet operation. They directly convert chemical energy into electrical energy through electrochemical reactions, with high efficiency and almost no pollutant emissions. Among them, proton exchange membrane fuel cells (PEMFC) are widely used in transportation, portable devices, and fixed power sources due to their fast start-up, high power density, and low operating temperature. As the core component of PEMFC, the membrane electrode (MEA) determines the performance and life of the battery, and the most critical part of the membrane electrode is the catalyst coated membrane (CCM), which directly affects the efficiency and stability of the electrochemical reaction.

[0003] Commercial platinum-carbon (Pt / C) catalyst is one of the key materials for preparing CCM. The active component Pt is adsorbed on the carrier C through physical action. Pt is a rare and expensive precious metal. In order to reduce the usage of Pt while maintaining the high performance of CCM, Pt is designed into 2-5nm particles and grown on the carrier C. The particle size range of 2-5nm can be compatible with the catalytic activity and dimensional stability of Pt nanoparticles to a large extent. Pt nanoparticles that are too small will increase the risk of agglomeration, and Pt nanoparticles that are too large will reduce the number density of active sites. Commonly used commercial fuel cell catalysts all use carbon-based carriers, which are a classic type of carrier material that can provide a high specific surface area (>100m 2 / g) and high conductivity (>1S / cm@usually less than 10MPa); in addition, low cost is another advantage of carbon-based carriers;

[0004] However, a major drawback of carbon-based carriers is their poor stability. In the harsh operating environment of fuel cells (pH range 0-2, potential range 0-1.5V), carbon-based carriers face severe chemical corrosion and potential corrosion.

[0005] Regarding the chemical corrosion mechanism, the carbon carrier is in a strong acidic and oxidizing working environment at the anode and cathode of the fuel cell for a long time, which poses a significant threat to the service life of the carbon carrier. First, a large amount of H + It will gradually corrode the micropores and mesoporous structures in the anode carbon carrier, reducing the specific surface area of ​​the carbon carrier. This will reduce the dispersibility of platinum nanoparticles, thereby reducing their effective active area; secondly, long-term acid corrosion will cause the pore structure of the anode carbon carrier to collapse, and the mechanical strength will decrease, thus affecting the stability and durability of the membrane electrode assembly; thirdly, the oxidizing intermediate species of the cathode will promote carbon corrosion, weaken the porous structure of the carbon carrier, and cause the Pt nanoparticles to fall off and agglomerate;

[0006] Regarding the high potential corrosion mechanism; under normal working conditions, the hydrogen oxidation reaction proceeds rapidly, and the anode electrode is in a stable state of 0V; when a membrane electrode is insufficiently supplied with hydrogen at the anode due to various reasons, the membrane electrode will produce a reverse polarity phenomenon; during the actual operation of the on-board proton exchange membrane fuel cell, the phenomenon of complete hydrogen shortage is caused by various factors such as cold start, improper operation, failure of auxiliary system components, poor software control strategy, anode flooding, unreasonable flow field design, uneven plate processing, uneven stack assembly, and rapid load cycle; when the hydrogen is cut off after shutdown, the oxygen in the air will gradually pass through the proton exchange membrane to the anode side. When the PEMFC is restarted after being stationary for a long time, a hydrogen-air interface will be formed at one or several membrane electrode anodes, resulting in a phenomenon of partial shortage of hydrogen at the anode;

[0007] When the anode of a membrane electrode is completely lacking in hydrogen supply, the hydrogen oxidation reaction cannot proceed normally. The membrane electrode will be charged by the two healthy membrane electrodes connected to it, which will cause the anode potential of the membrane electrode to rise rapidly to 1-1.5V; if the anode is seriously lacking in hydrogen, the anode potential will even exceed 1.5V; the membrane electrode will produce a reverse polarity phenomenon, which is specifically manifested in that the voltage of the membrane electrode becomes negative; the high potential of the anode will cause the carbon carrier of the anode catalyst to face severe corrosion, C+2H2O→CO2+4H + +4e - ; The high potential of the anode will significantly increase the thermodynamic driving force for the oxidation of the anode carbon carrier, and the carbon corrosion reaction rate will be further increased under high temperature and high humidity conditions. This will cause the structural collapse of the carbon carrier, resulting in the loss of support and the detachment or agglomeration of Pt nanoparticles; the pore structure of the catalyst layer is destroyed, and the electronic conductivity and gas transport performance are significantly reduced; in addition, the carbon corrosion reaction at the anode will produce local hot spots, further aggravating the chemical and high-potential corrosion of the material. When the anode part of a membrane electrode lacks hydrogen supply, a normal forward current is formed in the hydrogen-rich region of the membrane electrode anode, which will charge the oxygen-rich region of the membrane electrode anode to form a "galvanic cell-electrolytic cell" structure. At this time, an abnormal reverse current will be generated in the oxygen-rich region, and the potential of the cathode will increase to a value about twice the open circuit potential, which will cause corrosion of the cathode carbon carrier. The electrochemical corrosion of the cathode carbon carrier will cause the detachment and agglomeration of platinum nanoparticles, further causing a reduction in the electrochemical active area of ​​the catalyst; the detached platinum nanoparticles will be electrically isolated and unable to exert catalytic activity. Summary of the invention

[0008] In view of the above problems, the present invention provides a catalyst coated membrane. The membrane electrode assembled using the catalyst coated membrane has very good durability and has the dual functions of resisting complete anode gas deficiency and partial anode gas deficiency.

[0009] A catalyst coated membrane, the technical scheme of which is as follows, comprises a proton exchange membrane, an anode catalyst layer, and a cathode catalyst layer, wherein one surface of the proton exchange membrane is coated with the anode catalyst layer, and the other surface of the proton exchange membrane is coated with the cathode catalyst layer, the anode catalyst layer is obtained by spraying an anode spray slurry on one surface of the proton exchange membrane, and the cathode catalyst layer is obtained by spraying a cathode spray slurry on the other surface of the proton exchange membrane, characterized in that:

[0010] The anode spraying slurry is composed of a mixture of an anode slurry and an anode anti-reverse slurry, the anode slurry is composed of a dispersant and a dispersoid, the dispersant of the anode slurry is ultrapure water and isopropanol, the dispersoid of the anode slurry is a dry resin and an anode catalyst Pt / Ti4O7, and the solid content of the anode slurry after mixing is 1% to 2%; the anode anti-reverse slurry is composed of a dispersant and a dispersoid, the dispersant of the anode anti-reverse slurry is ultrapure water and isopropanol, the dispersoid of the anode anti-reverse slurry is a dry resin and an anode anti-reverse catalyst IrO2 / Ti4O7, and the solid content of the anode anti-reverse slurry after mixing is 1% to 2%;

[0011] The cathode spraying slurry consists of cathode slurry and cathode anti-reverse pole slurry. The cathode slurry consists of a dispersant and a dispersant. The dispersant of the cathode slurry is ultrapure water and isopropyl alcohol. The dispersant of the cathode slurry is a dry resin and a cathode catalyst Pt / W-SnO2. After mixing, the solid content of the cathode slurry is 1% to 2%. The cathode anti-reverse pole slurry consists of a dispersant and a dispersant. The dispersant of the cathode anti-reverse pole slurry is ultrapure water and isopropyl alcohol. The dispersant of the cathode anti-reverse pole slurry is a dry resin and a cathode anti-reverse pole catalyst IrO2 / W-SnO2. After mixing, the solid content of the cathode anti-reverse pole slurry is 1% to 2%.

[0012] It is further characterized by:

[0013] The volume ratio of ultrapure water to isopropanol in the anode slurry is 1:1-4, and the mass ratio of dry resin to Pt / Ti4O7 is 21:50;

[0014] The volume ratio of ultrapure water and isopropanol in the anode anti-reverse slurry is 1:1-4, and the mass ratio of dry resin and IrO2 / Ti4O7 is 12:25;

[0015] The volume ratio of ultrapure water to isopropanol in the cathode slurry is 1:1-4, and the mass ratio of dry resin to Pt / W-SnO2 is 3:10;

[0016] The volume ratio of ultrapure water to isopropanol in the cathode anti-reverse electrode slurry is 1:1-4, and the mass ratio of dry resin to IrO2 / W-SnO2 is 12:25.

[0017] It is further characterized by:

[0018] Mixing 5 parts of anode slurry with 1 part of anode anti-reverse slurry to obtain anode spray slurry; mixing 20 parts of cathode slurry with 1 part of cathode anti-reverse slurry to obtain cathode spray slurry, and after the mixing is completed, slurry dispersion is performed on the anode spray slurry and the cathode spray slurry, and the slurry dispersion steps include pulping, grinding and ultrasound;

[0019] After the slurry dispersion of the anode spray slurry and the cathode spray slurry is completed, the preparation of the CCM is completed by the spraying machine.

[0020] A method for preparing a catalyst coated membrane, characterized in that it comprises the following steps:

[0021] S1, preparing Ti4O7, thereby obtaining anode catalyst Pt / Ti4O7 and anode anti-reverse catalyst IrO2 / Ti4O7;

[0022] S2, obtaining cathode catalyst Pt / W-SnO2 and cathode anti-reverse polarity catalyst IrO2 / W-SnO2 through W-SnO2;

[0023] S3, preparing anode slurry, cathode slurry, anode anti-reverse slurry, cathode anti-reverse slurry;

[0024] S4, 5 parts of anode slurry and 1 part of anode anti-reverse slurry are mixed to obtain anode spray slurry, and 20 parts of cathode slurry and 1 part of cathode anti-reverse slurry are mixed to obtain cathode spray slurry; after the mixing is completed, the anode spray slurry and the cathode spray slurry are slurry dispersed; the dispersion steps of the anode spray slurry and the cathode spray slurry both include pulping, grinding and ultrasound;

[0025] S5. After the anode spraying slurry and the cathode spraying slurry are dispersed, the catalyst coating membrane is prepared by a spraying machine.

[0026] It is further characterized by:

[0027] In step S1, after the preparation of Ti4O7 is completed, the anode catalyst Pt / Ti4O7 and the anode anti-reversal catalyst IrO2 / Ti4O7 need to be prepared through Ti4O7;

[0028] The preparation of the anode catalyst Pt / Ti4O7 includes the following steps:

[0029] S12, add diammine dinitrite platinum Pt(NO2)2(NH3)2 and 0.7 g of Ti4O7 carrier to 200 ml of distilled water, disperse for 1 hour by magnetic stirring, and adjust the amount of platinum precursor added so that the mass fraction of Pt in the final catalyst reaches 30%; stir to evenly suspend the Ti4O7 particles to increase the surface area to facilitate the platinum ion (Pt2+ ) adsorption;

[0030] Add 30 ml of ethanol and continue stirring at room temperature for 30 minutes; ethanol, as an auxiliary agent, changes the surface tension of the system, promotes the uniform adsorption of platinum ions on the surface of the carrier material Ti4O7, reduces the agglomeration of particles, and makes the catalyst precursor form a more uniform dispersion state;

[0031] The temperature was raised to 95°C and stirred for 12 hours to obtain a Pt / Ti4O7 catalyst. In this process, ethanol was mainly used as a reducing agent to convert platinum ions (Pt 2+ ) is reduced to platinum (Pt 0 ) nanoparticles; at the same time, ethanol as a solvent helps to stabilize the dispersion of the precursor and prevent the aggregation of particles;

[0032] The Pt / Ti4O7 catalyst was separated from the solution by vacuum filtration, washed with 1L of distilled water, and dried at room temperature for 12 hours; unreacted precursors, ethanol and other soluble impurities were removed by washing to ensure the purity of the catalyst; water was evaporated by drying at room temperature to form a preliminary solid structure, providing a stable foundation for subsequent heat treatment;

[0033] The Pt / Ti4O7 catalyst was dried at 80°C for 10 hours in a nitrogen atmosphere; the Pt / Ti4O7 catalyst was dried at 200°C for 2 hours in a helium atmosphere; low-temperature drying in a nitrogen environment was performed to remove physically adsorbed water or organic solvent residues remaining in the material; the temperature was raised to 200°C in a helium environment to improve the distribution uniformity and binding force of platinum nanoparticles on the Ti4O7 carrier and optimize the structure of the Pt / Ti4O7 catalyst; the inert environment of helium was used to avoid oxidation or further reduction of the particles and maintain the stability and activity of the Pt / Ti4O7 catalyst;

[0034] The preparation of the anode anti-reverse polarity catalyst IrO2 / Ti4O7 comprises the following steps:

[0035] S13, adding iridium chloride H2IrCl6 and 0.8 g of Ti4O7 carrier to 200 ml of distilled water, and dispersing them by magnetic stirring for 1 hour, while adjusting the amount of iridium precursor added so that the mass fraction of IrO2 in the final catalyst reaches 20%; stirring to uniformly suspend the Ti4O7 particles to increase the surface area to facilitate the iridium ion (Ir 4+ ) adsorption;

[0036] Add 50 ml of ethanol and continue stirring at room temperature for 60 minutes; ethanol, as an auxiliary agent, changes the surface tension of the system, promotes the uniform adsorption of iridium ions on the surface of the carrier material Ti4O7, reduces the agglomeration of particles, and makes the catalyst precursor form a more uniform dispersion state;

[0037] The temperature was raised to 90°C and stirred for 16 hours to obtain Ir / Ti4O7. Ethanol was mainly used as a reducing agent in this process to convert iridium ions (Ir 4+ ) is reduced to iridium (Ir 0 ) nanoparticles; at the same time, ethanol as a solvent helps to stabilize the dispersion of the precursor and prevent the aggregation of particles;

[0038] Ir / Ti4O7 was separated from the solution by vacuum filtration, washed with 1L of distilled water, and dried at room temperature for 12 hours; unreacted precursors, ethanol and other soluble impurities were removed by washing to ensure the purity of the material; water was evaporated by drying at room temperature to form a preliminary solid structure, providing a stable foundation for subsequent heat treatment;

[0039] The Ir / Ti4O7 material was dried at 80°C for 10 hours in a nitrogen atmosphere; the material was dried at low temperature in a nitrogen environment to remove the physically adsorbed water or organic solvent residues remaining in the material;

[0040] In a nitrogen / oxygen mixed atmosphere, the volume fraction ratio is φ(nitrogen):φ(oxygen)=95%:5%; and the Ir / Ti4O7 material is dried and oxidized at 200°C for 2 hours to obtain an IrO2 / Ti4O7 catalyst; oxidation and drying in a mixed atmosphere are performed, on the one hand, to form iridium dioxide nanoparticles (IrO2); on the other hand, to improve the distribution uniformity and binding force of the iridium dioxide nanoparticles on the Ti4O7 carrier.

[0041] Step S2 includes preparing cathode catalyst Pt / W-SnO2 and cathode anti-reversal catalyst IrO2 / W-SnO2 by W-SnO2;

[0042] The preparation of cathode catalyst Pt / W-SnO2 includes the following steps:

[0043] Platinum diamine dinitrite Pt(NO2)2(NH3)2 and 0.5 g of W-SnO2 carrier were added to 200 ml of distilled water and dispersed by magnetic stirring for 1 hour. At the same time, the amount of platinum precursor added was adjusted to make the mass fraction of Pt in the final catalyst reach 50%; the W-SnO2 particles were evenly suspended by stirring to increase the surface area to facilitate the platinum ion (Pt 2+ ) adsorption;

[0044] Add 50 ml of ethanol and continue stirring at room temperature for 60 minutes; ethanol, as an auxiliary agent, changes the surface tension of the system, promotes the uniform adsorption of platinum ions on the surface of the carrier material W-SnO2, reduces the agglomeration of particles, and makes the catalyst precursor form a more uniform dispersion state;

[0045] The temperature was raised to 90°C and stirred for 16 hours to obtain a Pt / W-SnO2 catalyst. Ethanol was mainly used as a reducing agent in this process to convert platinum ions (Pt 2+ ) is reduced to platinum (Pt 0 ) nanoparticles; at the same time, ethanol as a solvent helps to stabilize the dispersion of the precursor and prevent the aggregation of particles;

[0046] The Pt / W-SnO2 catalyst was separated from the solution by vacuum filtration, washed with 1L of distilled water, and dried at room temperature for 12 hours; unreacted precursors, ethanol, and other soluble impurities were removed by washing to ensure the purity of the catalyst; water was evaporated by drying at room temperature to form a preliminary solid structure, providing a stable foundation for subsequent heat treatment;

[0047] The Pt / W-SnO2 catalyst was dried at 80°C for 10 hours in a nitrogen atmosphere; the catalyst was dried at low temperature in a nitrogen environment to remove the physically adsorbed water or organic solvent residues remaining in the material;

[0048] In a helium atmosphere, the Pt / W-SnO2 catalyst was dried at 200°C for 2 hours; the temperature was raised to 200°C in a helium environment to improve the distribution uniformity and binding force of platinum nanoparticles on the W-SnO2 carrier and optimize the structure of the Pt / W-SnO2 catalyst; the inert environment of helium was used to avoid oxidation or further reduction of the particles and maintain the stability and activity of the Pt / W-SnO2 catalyst;

[0049] The preparation of the cathode anti-reversal catalyst IrO2 / W-SnO2 comprises the following steps:

[0050] Chloroiridic acid H2IrCl6 and 0.8 g of Ti4O7 carrier were added to 200 ml of distilled water and dispersed by magnetic stirring for 1 hour. At the same time, the amount of iridium precursor added was adjusted to make the mass fraction of IrO2 in the final catalyst reach 20%; Ti4O7 particles were evenly suspended by stirring to increase the surface area to facilitate the iridium ion (Ir 4+ ) adsorption;

[0051] Add 50 ml of ethanol and continue stirring at room temperature for 60 minutes; ethanol, as an auxiliary agent, changes the surface tension of the system, promotes the uniform adsorption of iridium ions on the surface of the carrier material Ti4O7, reduces the agglomeration of particles, and makes the catalyst precursor form a more uniform dispersion state;

[0052] The temperature was raised to 90°C and stirred for 16 hours to obtain Ir / Ti4O7. Ethanol was mainly used as a reducing agent in this process to convert iridium ions (Ir 4+ ) is reduced to iridium (Ir 0 ) nanoparticles; at the same time, ethanol as a solvent helps to stabilize the dispersion of the precursor and prevent the aggregation of particles;

[0053] Ir / Ti4O7 was separated from the solution by vacuum filtration, washed with 1L of distilled water, and dried at room temperature for 12 hours; unreacted precursors, ethanol and other soluble impurities were removed by washing to ensure the purity of the material; water was evaporated by drying at room temperature to form a preliminary solid structure, providing a stable foundation for subsequent heat treatment;

[0054] The Ir / Ti4O7 material was dried at 80°C for 10 hours in a nitrogen atmosphere; the material was dried at low temperature in a nitrogen environment to remove the physically adsorbed water or organic solvent residues remaining in the material;

[0055] In a nitrogen / oxygen mixed atmosphere, the volume fraction ratio is φ(nitrogen):φ(oxygen)=95%:5%; and the Ir / Ti4O7 material is dried and oxidized at 200°C for 2 hours to obtain an IrO2 / Ti4O7 catalyst; oxidation and drying in a mixed atmosphere are performed, on the one hand, to form iridium dioxide nanoparticles (IrO2); on the other hand, to improve the distribution uniformity and binding force of the iridium dioxide nanoparticles on the Ti4O7 carrier.

[0056] In step S3, four slurries including anode slurry, cathode slurry, anode anti-reverse slurry and cathode anti-reverse slurry are mixed and obtained;

[0057] Step S31, mixing and obtaining anode slurry, wherein the volume ratio of ultrapure water and isopropanol in the anode slurry is 1:1-4, the mass ratio of dry resin and Pt / Ti4O7 is 21:50, and the solid content in the anode slurry after mixing is 1%-2%;

[0058] Step S32, mixing and obtaining cathode slurry, wherein the volume ratio of ultrapure water and isopropanol in the cathode slurry is 1:1-4, the mass ratio of dry resin and Pt / W-SnO2 is 3:10, and the solid content in the cathode slurry after mixing is 1%-2%;

[0059] Step S33, mixing and obtaining anode anti-reverse electrode slurry, wherein the volume ratio of ultrapure water and isopropanol in the anode anti-reverse electrode slurry is 1:1-4, the mass ratio of dry resin and IrO2 / Ti4O7 is 12:25, and the solid content in the anode anti-reverse electrode slurry after mixing is 1%-2%;

[0060] Step S34, cathode anti-reverse electrode slurry is obtained by mixing, wherein the volume ratio of ultrapure water and isopropyl alcohol in the cathode anti-reverse electrode slurry is 1:1-4, the mass ratio of dry resin and IrO2 / W-SnO2 is 12:25, and the solid content in the cathode anti-reverse electrode slurry after mixing is 1%-2%.

[0061] In step S4, the anode spray slurry and the cathode spray slurry use the same dispersion equipment and process parameters, and the specific pulping, grinding and ultrasonic process flow is as follows:

[0062] The pulping is completed by a pulping machine, the speed of the mechanical stirring blade is set to 40r / min, the power of the rod-type ultrasonic crusher is set to 800W, the frequency is set to 20kHz, the speed of the high-speed shearing machine is set to 18000r / min, the temperature of the coolant of the water-cooling unit is set to 15℃±1℃, and the pulping time is set to 20min;

[0063] The grinding is completed by a grinder, the rotation speed of the grinding rod is set to 3.1 m / s, zirconium dioxide grinding beads with φ=0.03 mm are selected, the temperature of the coolant of the water-cooling unit is set to 15°C±1°C, and the pulping time is set to 20 min.

[0064] Ultrasonic cleaning was performed by a tank-type constant temperature ultrasonic cleaning machine, the ultrasonic power was set to 750W, the temperature of the coolant in the water-cooling unit was controlled at 15℃±1℃, and the ultrasonic time was set to 20min;

[0065] After dispersion, the anode spray slurry and cathode spray slurry are obtained respectively; then the particle size is detected by a laser nanoparticle size analyzer; if the particle size meets (D 50 ≤1μm, D 90 ≤2μm, D 99 ≤2.4μm, the next spraying process can be carried out; if the particle size does not meet the technical requirements, the slurry must be re-dispersed.

[0066] The preparation method of Ti4O7 is characterized in that the Ti4O7 carrier material is prepared by a titanyl sulfate-polyethylene glycol reduction method, which comprises the following steps:

[0067] A beaker is placed in a fume hood, and a mixed solvent is added to the beaker, wherein the mixed solvent consists of deionized water and polyethylene glycol, wherein the molecular weight range of the polyethylene glycol is 360-440 and the average molecular weight is 400, and solid titanium oxysulfate (TiOSO4) is weighed and dissolved in the beaker, so that the titanium oxysulfate is dispersed at room temperature, and the derivative of titanium oxysulfate (TiOSO4) decomposed at room temperature includes titanium dioxide, so that the mass ratio of polyethylene glycol to titanium dioxide in the mixed solvent is 1:1; at room temperature, the initial state of the dispersion is white;

[0068] An aluminum bathtub is placed in a fume hood, and a beaker containing titanyl sulfate and a mixed solvent is placed in the bathtub; aluminum beads are added to the bathtub as a heat-conducting medium, magnetic stirring is started, and the system is heated and maintained at a heating temperature while stirring continuously; during the heating process, the white dispersion gradually turns into a yellow solution until the solution further turns into a brown gel;

[0069] The magnetic stirring was continued, and the heating temperature of the aluminum bathtub was further increased to 150°C and maintained at this temperature for 5 h. During the heating period, the brown gel gradually transformed into a black powder.

[0070] After the black powder in the beaker has cooled to room temperature, it is fully ground using an agate mortar, and the ground powder is transferred to an alumina boat and sealed in a quartz tube;

[0071] The sealed quartz tube was taken out from the fume hood and placed in a tube furnace. Before heating in the tube furnace, the quartz tube was purged with N2 to exhaust the residual air in the tube. Then the gas flow was switched and a H2 / Ar mixed gas was introduced. The sample was heated from room temperature to 967°C at a heating rate of 10°C / min and maintained at this temperature for 3h to obtain Ti4O7.

[0072] Titanyl sulfate is a cheap titanium source widely used in industry, and its price is more competitive than commercial TiO2 or some high-purity chemicals. Deionized water is used as the solvent in the process, and there is no need to use expensive organic solvents such as ethanol and isopropanol, which significantly reduces material and production costs. Titanyl sulfate has good chemical stability to moisture in the environment, which makes it easier to manage during storage and handling. During the dispersion, dissolution and gelation process, no special anhydrous or inert atmosphere protection is required, which greatly simplifies the experimental conditions. By increasing the mass of titanyl sulfate and polyethylene glycol, the large-scale preparation of Ti4O7 can be easily achieved without changing the equipment or process conditions. The good dispersibility and hydrolysis characteristics of titanyl sulfate in the solution make the particles evenly distributed during the preparation process, which is suitable for continuous production.

[0073] The heat preservation process promotes the dissolution and hydrolysis reaction of titanyl sulfate to generate nano-scale colloidal titanium dioxide (TiO2·xH2O); polyethylene glycol gradually coats the nano-scale titanium dioxide colloidal particles within the temperature range and forms a stable gel network structure; this lays the foundation for the uniform reduction and particle control of Ti4O7 in the subsequent heat treatment; the Ti4O7 powder prepared by the present invention is characterized by nitrogen adsorption isotherm at 77K using a surface area and pore size distribution analyzer, and its specific surface area is 172m 2 / g, which is close to the 251m 2 / g; The Ti4O7 powder prepared by the present invention was characterized by field emission scanning electron microscopy, such as Figure 2 As shown, the diameter of its Ti4O7 carrier particles is about 60-70nm, and high specific surface area is one of the necessary conditions for being used as a fuel cell catalyst carrier material;

[0074] The crystal structure of Ti4O7 consists of three layers of TiO2 and one layer of TiO arranged alternately; TiO2 is a thermodynamically extremely stable material. 4+The binding energy between ions and oxygen is high, and it is difficult to be oxidized or reduced; in strong acid, strong alkali and electrochemical environments, the TiO2 surface exhibits excellent anti-oxidation and anti-reduction capabilities; the TiO2 layer is distributed alternately with the TiO layer in the crystal, forming an effective protective barrier for the TiO layer to prevent it from direct contact with the corrosive medium; the TiO2 layer exhibits a high corrosion potential in acidic and alkaline environments, and is difficult to dissolve or react chemically; Ti 2+ It has two unpaired d electrons, which can participate in charge transfer and conduction. The TiO layer is evenly distributed in the Ti4O7 crystal, and its continuity provides a quasi-two-dimensional electron transmission path. This geometric arrangement is conducive to reducing the scattering effect of electrons, thereby improving the conductivity.

[0075] The conductivity of the Ti4O7 carrier material prepared by the titanyl sulfate-polyethylene glycol reduction method is closely related to the phase purity of Ti4O7. After repeated experiments, the inventors determined the optimal reaction conditions: "First, the mass ratio of polyethylene glycol with an average relative molecular mass of 400 to titanium dioxide, a derivative of titanyl sulfate, must be 1:1, otherwise the phase purity of Ti4O7 will be reduced; second, the gel drying conditions need to be maintained at 150°C and 5h to balance the volatilization of sulfides and the particle size of nano-scale TiO2 precursors; too low a temperature will cause the sulfide to not be completely volatilized, and the subsequent reduction step cannot be carried out; too high a temperature will cause Ti The particle size of the O2 precursor is too large, which reduces the specific surface area of ​​the subsequent Ti4O7 carrier material; thirdly, the heat treatment conditions need to be maintained at 967°C and 3h. Too high or too low a heat treatment temperature will reduce the phase purity of Ti4O7, and too long a heat treatment time will reduce the specific surface area of ​​Ti4O7; the conductivity of the Ti4O7 carrier material prepared by the present invention was measured by a powder resistivity measurement system using a four-probe method at a compression pressure ranging from 3-64MPa, and the value was 1.2S / cm, which is very close to the classic carbon-based carrier XC-72R; high conductivity is one of the necessary conditions for a fuel cell catalyst carrier material.

[0076] After adopting the present invention, the membrane electrode assembled by adopting the catalyst coating membrane has very good durability and has the dual functions of resisting complete anode gas shortage and partial anode gas shortage. BRIEF DESCRIPTION OF THE DRAWINGS

[0077] Figure 1 It is a magnified schematic diagram of commercial platinum carbon (Pt / C);

[0078] Figure 2 It is an enlarged schematic diagram of Ti4O7 carrier particles;

[0079] Figure 3 It is a schematic diagram of the structure of a pulping machine used in the preparation method of the present invention;

[0080] Figure 4 A schematic diagram of the structure of a grinding machine used in the preparation method of the present invention;

[0081] Figure 5 Polarization curve characterization diagram for membrane electrodes A, B, C and D;

[0082] Figure 6 Polarization curve characterization diagram for membrane electrodes E, F and G;

[0083] Figure 7 Comparison diagram of polarization curves A', B', C' and D' of membrane electrodes A, B, C and D after 10,000 cycles;

[0084] Figure 8 The graph is the anti-reverse polarity test result of membrane electrode E and membrane electrode G under the condition of complete anode gas deficiency;

[0085] Fig. 9 This is the anti-reverse polarity test result diagram of membrane electrode E and membrane electrode F under the condition of partial gas deficiency in the anode. DETAILED DESCRIPTION

[0086] A catalyst-coated membrane: comprising a proton exchange membrane, an anode catalyst layer, and a cathode catalyst layer, wherein one surface of the proton exchange membrane is coated with the anode catalyst layer, and the other surface of the proton exchange membrane is coated with the cathode catalyst layer, wherein the anode catalyst layer is obtained by spraying an anode spray slurry on one surface of the proton exchange membrane, and the cathode catalyst layer is obtained by spraying a cathode spray slurry on the other surface of the proton exchange membrane;

[0087] The anode spraying slurry is composed of a mixture of an anode slurry and an anode anti-reverse slurry, the anode slurry is composed of a dispersant and a dispersoid, the dispersant of the anode slurry is ultrapure water and isopropanol, the dispersoid of the anode slurry is a dry resin and an anode catalyst Pt / Ti4O7, and the solid content of the anode slurry after mixing is 1% to 2%; the anode anti-reverse slurry is composed of a dispersant and a dispersoid, the dispersant of the anode anti-reverse slurry is ultrapure water and isopropanol, the dispersoid of the anode anti-reverse slurry is a dry resin and an anode anti-reverse catalyst IrO2 / Ti4O7, and the solid content of the anode anti-reverse slurry after mixing is 1% to 2%;

[0088] The cathode spraying slurry consists of cathode slurry and cathode anti-reverse pole slurry. The cathode slurry consists of a dispersant and a dispersant. The dispersant of the cathode slurry is ultrapure water and isopropyl alcohol. The dispersant of the cathode slurry is a dry resin and a cathode catalyst Pt / W-SnO2. After mixing, the solid content of the cathode slurry is 1% to 2%. The cathode anti-reverse pole slurry consists of a dispersant and a dispersant. The dispersant of the cathode anti-reverse pole slurry is ultrapure water and isopropyl alcohol. The dispersant of the cathode anti-reverse pole slurry is a dry resin and a cathode anti-reverse pole catalyst IrO2 / W-SnO2. After mixing, the solid content of the cathode anti-reverse pole slurry is 1% to 2%.

[0089] In a specific embodiment, catalysts [Pt / Ti4O7 (30%), IrO2 / Ti4O7 (20%), Pt / W-SnO2 (50%), IrO2 / W-SnO2 (20%)], ionomer resin emulsion, isopropyl alcohol and ultrapure water are mixed in a certain proportion to prepare a slurry; wherein the ionomer resin emulsion contains 20% of dry resin; the dry resin is specifically perfluorosulfonic acid dry resin.

[0090] The anode catalyst Pt / Ti4O7 corresponds to the anode slurry, the cathode catalyst Pt / W-SnO2 corresponds to the cathode slurry, the anode anti-reverse catalyst IrO2 / Ti4O7 corresponds to the anode anti-reverse slurry, and the cathode anti-reverse catalyst IrO2 / W-SnO2 corresponds to the cathode anti-reverse slurry; the proportions of each slurry are listed in Table 1; each slurry is a dispersion system, the catalyst and dry resin are dispersants, and the rest are dispersants; the specific proportions are shown in Table 1

[0091]

[0092] Anode spray slurry is obtained by mixing 5 parts of anode slurry with 1 part of anode anti-reverse slurry, and cathode spray slurry is obtained by mixing 20 parts of cathode slurry with 1 part of cathode anti-reverse slurry; after mixing, the anode spray slurry and cathode spray slurry are slurry dispersed; each slurry adopts the same dispersion equipment and process parameters; the whole slurry dispersion process is divided into 3 steps - pulping, grinding and ultrasound.

[0093] A method for preparing a catalyst coated membrane, characterized in that it comprises the following steps:

[0094] S1, preparing Ti4O7, thereby obtaining anode catalyst Pt / Ti4O7 and anode anti-reverse catalyst IrO2 / Ti4O7;

[0095] The working environment of the anode of the fuel cell is a high temperature, high humidity, strong acidity, and reducing atmosphere, while the working environment of the cathode of the fuel cell is a high temperature, high humidity, and strong oxidation. Since the conductive mechanism of Ti4O7 is relatively stable in a long-term reducing atmosphere, Ti4O7 is suitable as an anode material, so the Ti4O7 prepared by the present invention is used as an anode catalyst carrier; Pt / Ti4O7 is used as an anode catalyst;

[0096] When a high potential (1.0V to 2.0V) is generated due to lack of gas, the carbon-based material of the membrane electrode is thermodynamically unstable and "C+2H2O→CO2+4H + +4e - ” and “C+H2O→CO+2H + +2e - "; Carbon corrosion runs through the entire reverse polarity process, the thermodynamic equilibrium potential of the former is 0.207V, and the thermodynamic equilibrium potential of the latter is 0.518V; at the same time, the electrolysis reaction of water "2H2O→O2+4H + +4e - ", its thermodynamic equilibrium potential is 1.229V; it should be noted that the carbon oxidation reaction is thermodynamically favorable, but its kinetics are slow, while the water electrolysis reaction is kinetically favorable; since both the carbon oxidation reaction and the water electrolysis reaction require the participation of water, the two types of reactions are in a competitive relationship; the essence of the anti-reverse pole is "to promote the water electrolysis reaction, thereby inhibiting the carbon corrosion reaction", so the present invention selects iridium dioxide (IrO2) with relatively balanced activity and stability as the active component of the anti-reverse pole catalyst; when the anode of a certain membrane electrode is completely deficient in gas, the membrane electrode will be charged by the healthy membrane electrode (connected to it), and the anode of the membrane electrode will generate a high potential; on the one hand, in order to protect the anode catalyst layer, the present invention uses a long-life Ti4O7 carrier in the anode catalyst layer; on the other hand, in order to protect the anode gas diffusion layer, the present invention uses IrO2 active component in the anode; in summary, the anode anti-reverse pole catalyst selected by the present invention is IrO2 / Ti4O7;

[0097] S11, preparing Ti4O7, wherein the Ti4O7 carrier material is prepared by a titanyl sulfate-polyethylene glycol reduction method, which comprises the following steps:

[0098] Place the beaker in a fume hood and add 500 cm 3 A mixed solvent, wherein the mixed solvent is composed of deionized water and polyethylene glycol (molecular weight range 360-440, average molecular weight 400); 31.986 g of titanium oxysulfate (TiOSO4) solid is weighed and dissolved in a beaker, and the titanium oxysulfate is dispersed at room temperature; the mass ratio of polyethylene glycol to titanium dioxide (TiO2, a titanium oxysulfate derivative) in the mixed solvent is 1:1; at room temperature, the initial state of the dispersion is white;

[0099] An aluminum bathtub was placed in a fume hood, and a beaker containing titanyl sulfate and a mixed solvent was placed in the bathtub; aluminum beads were added to the bathtub as a heat-conducting medium, magnetic stirring was started, and the system was heated to 80°C; the temperature was maintained and stirring was continued for 14 hours; during the heating process, the white dispersion gradually turned into a yellow solution, and after 14 hours, the solution further turned into a brown gel;

[0100] The magnetic stirring was continued, and the heating temperature of the aluminum bathtub was further increased to 150°C and maintained at this temperature for 5 h; during the heating period, the brown gel gradually transformed into a black powder;

[0101] After the black powder in the beaker has cooled to room temperature, grind it thoroughly using an agate mortar. Transfer the ground powder to an alumina boat and seal it in a quartz tube;

[0102] The sealed quartz tube was taken out from the fume hood and placed in a tube furnace; before heating in the tube furnace, the quartz tube was purged with N2 for 20 minutes to exhaust the residual air in the tube; then the gas flow was switched to introduce a H2 / Ar mixed gas with a volume ratio of 10%:90%; the sample was heated from room temperature to 967°C at a heating rate of 10°C / min and maintained at this temperature for 3 hours to obtain Ti4O7;

[0103] S12, preparation of anode catalyst Pt / Ti4O7, comprising the following steps:

[0104] Platinum diamine dinitrite Pt(NO2)2(NH3)2 and 0.7 g of Ti4O7 carrier were added to 200 ml of distilled water and dispersed by magnetic stirring for 1 hour. At the same time, the amount of platinum precursor added was adjusted to make the mass fraction of Pt in the final catalyst reach 30%; Ti4O7 particles were evenly suspended by stirring to increase the surface area to facilitate the platinum ion (Pt 2+ ) adsorption;

[0105] Add 30 ml of ethanol and continue stirring at room temperature for 30 minutes; ethanol, as an auxiliary agent, changes the surface tension of the system, promotes the uniform adsorption of platinum ions on the surface of the carrier material Ti4O7, reduces the agglomeration of particles, and makes the catalyst precursor form a more uniform dispersion state;

[0106] The temperature was raised to 95°C and stirred for 12 hours to obtain a Pt / Ti4O7 catalyst. In this process, ethanol was mainly used as a reducing agent to convert platinum ions (Pt 2+ ) is reduced to platinum (Pt 0 ) nanoparticles; at the same time, ethanol as a solvent helps to stabilize the dispersion of the precursor and prevent the aggregation of particles;

[0107] The Pt / Ti4O7 catalyst was separated from the solution by vacuum filtration, washed with 1L of distilled water, and dried at room temperature for 12 hours; unreacted precursors, ethanol, and other soluble impurities were removed by washing to ensure the purity of the catalyst; water was evaporated by drying at room temperature to form a preliminary solid structure, providing a stable foundation for subsequent heat treatment

[0108] The Pt / Ti4O7 catalyst was dried at 80°C for 10 hours in a nitrogen atmosphere; the Pt / Ti4O7 catalyst was dried at 200°C for 2 hours in a helium atmosphere; low-temperature drying in a nitrogen environment was performed to remove physically adsorbed water or organic solvent residues remaining in the material; the temperature was raised to 200°C in a helium environment to improve the distribution uniformity and binding force of platinum nanoparticles on the Ti4O7 carrier and optimize the structure of the Pt / Ti4O7 catalyst; the inert environment of helium was used to avoid oxidation or further reduction of the particles and maintain the stability and activity of the Pt / Ti4O7 catalyst;

[0109] S13, preparation of anode anti-reverse polarity catalyst IrO2 / Ti4O7, comprising the following steps:

[0110] Chloroiridic acid H2IrCl6 and 0.8 g of Ti4O7 carrier were added to 200 ml of distilled water and dispersed by magnetic stirring for 1 hour. At the same time, the amount of iridium precursor added was adjusted to make the mass fraction of IrO2 in the final catalyst reach 20%; Ti4O7 particles were evenly suspended by stirring to increase the surface area to facilitate the iridium ion (Ir 4+ ) adsorption;

[0111] Add 50 ml of ethanol and continue stirring at room temperature for 60 minutes; ethanol, as an auxiliary agent, changes the surface tension of the system, promotes the uniform adsorption of iridium ions on the surface of the carrier material Ti4O7, reduces the agglomeration of particles, and makes the catalyst precursor form a more uniform dispersion state;

[0112] The temperature was raised to 90°C and stirred for 16 hours to obtain Ir / Ti4O7. Ethanol was mainly used as a reducing agent in this process to convert iridium ions (Ir 4+ ) is reduced to iridium (Ir 0 ) nanoparticles; at the same time, ethanol as a solvent helps to stabilize the dispersion of the precursor and prevent the aggregation of particles;

[0113] Ir / Ti4O7 was separated from the solution by vacuum filtration, washed with 1L of distilled water, and dried at room temperature for 12 hours; unreacted precursors, ethanol and other soluble impurities were removed by washing to ensure the purity of the material; water was evaporated by drying at room temperature to form a preliminary solid structure, providing a stable foundation for subsequent heat treatment;

[0114] The Ir / Ti4O7 material was dried at 80°C for 10 hours in a nitrogen atmosphere; the material was dried at low temperature in a nitrogen environment to remove the physically adsorbed water or organic solvent residues remaining in the material;

[0115] In a nitrogen / oxygen mixed atmosphere, the volume fraction ratio is "φ(nitrogen):φ(oxygen)=95%:5%"; and the Ir / Ti4O7 material is dried and oxidized at 200°C for 2 hours to obtain an IrO2 / Ti4O7 catalyst; the oxidation and drying in the mixed atmosphere are performed, on the one hand, to form iridium dioxide nanoparticles (IrO2); on the other hand, to improve the distribution uniformity and binding force of the iridium dioxide nanoparticles on the Ti4O7 carrier;

[0116] S2, obtaining cathode catalyst Pt / W-SnO2 and cathode anti-reverse polarity catalyst IrO2 / W-SnO2 through W-SnO2;

[0117] Since the conductive mechanism of tungsten-doped tin dioxide (W-SnO2, the mass fraction of W is 3%) is relatively stable in a long-term oxidizing atmosphere, tungsten-doped tin dioxide is very suitable as a cathode material. Using Pt / W-SnO2 as a cathode catalyst, after shutdown and hydrogen is cut off, the oxygen in the air will gradually pass through the proton exchange membrane to reach the anode side. When the fuel cell is restarted after a long period of static state, a hydrogen-air interface will be formed at one or several membrane electrode anodes. The anodes of these membrane electrodes will have hydrogen-rich areas and oxygen-rich areas, which is a phenomenon of partial gas shortage at the anode. A normal forward current is formed in the hydrogen-rich area of ​​the membrane electrode anode, and the forward current will charge the oxygen-rich area of ​​the membrane electrode anode to form a "galvanic cell-electrolytic cell" structure. At this time, the oxygen-rich area will generate an abnormal reverse current, and the potential of the cathode will increase to a value about twice the open circuit potential, which will cause corrosion of the cathode catalyst layer and the gas diffusion layer; on the one hand, to protect the cathode catalyst layer, the present invention uses a long-life W-SnO2 carrier in the cathode catalyst layer; on the other hand, to protect the cathode gas diffusion layer, the present invention uses an IrO2 active component in the cathode; in summary, the cathode anti-reverse polarity catalyst selected by the present invention is IrO2 / W-SnO2;

[0118] The preparation of cathode catalyst Pt / W-SnO2 includes the following steps:

[0119] Platinum diamine dinitrite Pt(NO2)2(NH3)2 and 0.5 g of W-SnO2 carrier were added to 200 ml of distilled water and dispersed by magnetic stirring for 1 hour. At the same time, the amount of platinum precursor added was adjusted to make the mass fraction of Pt in the final catalyst reach 50%; the W-SnO2 particles were evenly suspended by stirring to increase the surface area to facilitate the platinum ion (Pt 2+ ) adsorption;

[0120] Add 50 ml of ethanol and continue stirring at room temperature for 60 minutes; ethanol, as an auxiliary agent, changes the surface tension of the system, promotes the uniform adsorption of platinum ions on the surface of the carrier material W-SnO2, reduces the agglomeration of particles, and makes the catalyst precursor form a more uniform dispersion state;

[0121] The temperature was raised to 90°C and stirred for 16 hours to obtain a Pt / W-SnO2 catalyst. Ethanol was mainly used as a reducing agent in this process to convert platinum ions (Pt 2+ ) is reduced to platinum (Pt 0 ) nanoparticles; at the same time, ethanol as a solvent helps to stabilize the dispersion of the precursor and prevent the aggregation of particles;

[0122] The Pt / W-SnO2 catalyst was separated from the solution by vacuum filtration, washed with 1L of distilled water, and dried at room temperature for 12 hours; unreacted precursors, ethanol, and other soluble impurities were removed by washing to ensure the purity of the catalyst; water was evaporated by drying at room temperature to form a preliminary solid structure, providing a stable foundation for subsequent heat treatment;

[0123] The Pt / W-SnO2 catalyst was dried at 80°C for 10 hours in a nitrogen atmosphere; the catalyst was dried at low temperature in a nitrogen environment to remove the physically adsorbed water or organic solvent residues remaining in the material;

[0124] In a helium atmosphere, the Pt / W-SnO2 catalyst was dried at 200°C for 2 hours; the temperature was raised to 200°C in a helium environment to improve the distribution uniformity and binding force of platinum nanoparticles on the W-SnO2 carrier and optimize the structure of the Pt / W-SnO2 catalyst; the inert environment of helium was used to avoid oxidation or further reduction of the particles and maintain the stability and activity of the Pt / W-SnO2 catalyst;

[0125] The preparation of the cathode anti-reversal catalyst IrO2 / W-SnO2 comprises the following steps:

[0126] Chloroiridic acid H2IrCl6 and 0.8 g of Ti4O7 carrier were added to 200 ml of distilled water and dispersed by magnetic stirring for 1 hour. At the same time, the amount of iridium precursor added was adjusted to make the mass fraction of IrO2 in the final catalyst reach 20%; Ti4O7 particles were evenly suspended by stirring to increase the surface area to facilitate the iridium ion (Ir 4+ ) adsorption;

[0127] Add 50 ml of ethanol and continue stirring at room temperature for 60 minutes; ethanol, as an auxiliary agent, changes the surface tension of the system, promotes the uniform adsorption of iridium ions on the surface of the carrier material Ti4O7, reduces the agglomeration of particles, and makes the catalyst precursor form a more uniform dispersion state;

[0128] The temperature was raised to 90°C and stirred for 16 hours to obtain Ir / Ti4O7. Ethanol was mainly used as a reducing agent in this process to convert iridium ions (Ir 4+ ) is reduced to iridium (Ir 0 ) nanoparticles; at the same time, ethanol as a solvent helps to stabilize the dispersion of the precursor and prevent the aggregation of particles;

[0129] Ir / Ti4O7 was separated from the solution by vacuum filtration, washed with 1L of distilled water, and dried at room temperature for 12 hours; unreacted precursors, ethanol and other soluble impurities were removed by washing to ensure the purity of the material; water was evaporated by drying at room temperature to form a preliminary solid structure, providing a stable foundation for subsequent heat treatment;

[0130] The Ir / Ti4O7 material was dried at 80°C for 10 hours in a nitrogen atmosphere; the material was dried at low temperature in a nitrogen environment to remove the physically adsorbed water or organic solvent residues remaining in the material;

[0131] In a nitrogen / oxygen mixed atmosphere, the volume fraction ratio is "φ(nitrogen):φ(oxygen)=95%:5%"; and the Ir / Ti4O7 material is dried and oxidized at 200°C for 2 hours to obtain an IrO2 / Ti4O7 catalyst; oxidation and drying in a mixed atmosphere are carried out, on the one hand, to form iridium dioxide nanoparticles (IrO2); on the other hand, to improve the distribution uniformity and binding force of iridium dioxide nanoparticles on the Ti4O7 carrier.

[0132] S3, preparing anode slurry, cathode slurry, anode anti-reverse slurry, cathode anti-reverse slurry;

[0133] Step S31, mixing and obtaining anode slurry, wherein the volume ratio of ultrapure water and isopropanol in the anode slurry is 1:1-4, the mass ratio of dry resin and Pt / Ti4O7 is 21:50, and the solid content in the anode slurry after mixing is 1%-2%;

[0134] Step S32, mixing and obtaining cathode slurry, wherein the volume ratio of ultrapure water and isopropanol in the cathode slurry is 1:1-4, the mass ratio of dry resin and Pt / W-SnO2 is 3:10, and the solid content in the cathode slurry after mixing is 1%-2%;

[0135] Step S33, mixing and obtaining anode anti-reverse electrode slurry, wherein the volume ratio of ultrapure water and isopropanol in the anode anti-reverse electrode slurry is 1:1-4, the mass ratio of dry resin and IrO2 / Ti4O7 is 12:25, and the solid content in the anode anti-reverse electrode slurry after mixing is 1%-2%;

[0136] Step S34, cathode anti-reverse electrode slurry is obtained by mixing, wherein the volume ratio of ultrapure water and isopropyl alcohol in the cathode anti-reverse electrode slurry is 1:1-4, the mass ratio of dry resin and IrO2 / W-SnO2 is 12:25, and the solid content in the cathode anti-reverse electrode slurry after mixing is 1%-2%.

[0137] S4, 5 parts of anode slurry and 1 part of anode anti-reverse slurry are mixed to obtain anode spray slurry, and 20 parts of cathode slurry and 1 part of cathode anti-reverse slurry are mixed to obtain cathode spray slurry; after the mixing is completed, the anode spray slurry and the cathode spray slurry are slurry dispersed; the dispersion steps of the anode spray slurry and the cathode spray slurry both include pulping, grinding and ultrasound;

[0138] The anode spray slurry and cathode spray slurry use the same dispersion equipment and process parameters. The specific pulping, grinding and ultrasonic process flow is as follows:

[0139] Pulping is done by a pulping machine, which consists of "mechanical stirring blades, a rod-type ultrasonic crusher and a high-speed shearing machine"; e.g. Figure 3 As shown, 1 is a mechanical stirring blade, 2 is a rod-type ultrasonic crusher, and 3 is a high-speed shearing machine; the temperature control function of the pulping machine is completed by the "temperature sensor and water cooling unit"; the speed of the mechanical stirring blade is set to 40r / min, the power of the rod-type ultrasonic crusher is set to 800W, the frequency is set to 20kHz, the speed of the high-speed shearing machine is set to 18000r / min, the temperature of the coolant of the water cooling unit is set to 15℃±1℃, and the pulping time is set to 20min

[0140] Grinding is done by a grinder, which consists of "grinding rods and grinding beads"; Figure 4 As shown, 4 is the tank body, 5 is the grinding rod, 6 is the grinding beads, and 7 is the interlayer of the tank wall; the temperature control function of the grinder is completed by the "temperature sensor and water cooling unit", and the coolant flows through the interlayer of the tank wall to cool the slurry; the rotation speed of the grinding rod is set to 3.1m / s, zirconium dioxide grinding beads with φ=0.03mm are selected, the temperature of the coolant of the water cooling unit is set to 15℃±1℃, and the slurry making time is set to 20min.

[0141] The ultrasonic cleaning machine is used for ultrasonic cleaning. The temperature control function of the ultrasonic cleaning machine is completed by the "temperature sensor and water cooling unit". The ultrasonic power is set to 750W, the temperature of the coolant of the water cooling unit is controlled to 15℃±1℃, and the ultrasonic time is set to 20min.

[0142] After dispersion, the anode spray slurry B and cathode spray slurry B are obtained respectively; then the particle size is detected by "laser nanoparticle size analyzer"; if the particle size meets the technical requirements (D 50 ≤1μm, D 90 ≤2μm, D 99≤2.4μm), the next step of spraying can be carried out; if the particle size does not meet the technical requirements, the slurry must be re-dispersed.

[0143] S5. After the anode spraying slurry and the cathode spraying slurry are dispersed, the catalyst coating membrane is prepared by a spraying machine.

[0144] Titanyl sulfate is a cheap titanium source widely used in industry, and its price is more competitive than commercial TiO2 or some high-purity chemicals. Deionized water is used as the solvent in the process, and there is no need to use expensive organic solvents such as ethanol and isopropanol, which significantly reduces material and production costs. Titanyl sulfate has good chemical stability to moisture in the environment, which makes it easier to manage during storage and handling. During the dispersion, dissolution and gelation process, no special anhydrous or inert atmosphere protection is required, which greatly simplifies the experimental conditions. By increasing the mass of titanyl sulfate and polyethylene glycol, the large-scale preparation of Ti4O7 can be easily achieved without changing the equipment or process conditions. The good dispersibility and hydrolysis characteristics of titanyl sulfate in the solution make the particles evenly distributed during the preparation process, which is suitable for continuous production.

[0145] The heat preservation process promotes the dissolution and hydrolysis reaction of titanyl sulfate to generate nano-scale colloidal titanium dioxide (TiO2·xH2O); polyethylene glycol gradually coats the nano-scale titanium dioxide colloidal particles within the temperature range and forms a stable gel network structure; this lays the foundation for the uniform reduction and particle control of Ti4O7 in the subsequent heat treatment; the Ti4O7 powder prepared by the present invention is characterized by nitrogen adsorption isotherm at 77K using a surface area and pore size distribution analyzer, and its specific surface area is 172m 2 / g, which is close to the 251m 2 / g; The Ti4O7 powder prepared by the present invention was characterized by field emission scanning electron microscopy, such as Figure 2 As shown, the diameter of its Ti4O7 carrier particles is about 60-70nm, and high specific surface area is one of the necessary conditions for being used as a fuel cell catalyst carrier material;

[0146] The crystal structure of Ti4O7 consists of three layers of TiO2 and one layer of TiO arranged alternately; TiO2 is a thermodynamically extremely stable material. 4+ The binding energy between ions and oxygen is high, and it is difficult to be oxidized or reduced; in strong acid, strong alkali and electrochemical environments, the TiO2 surface exhibits excellent anti-oxidation and anti-reduction capabilities; the TiO2 layer is distributed alternately with the TiO layer in the crystal, forming an effective protective barrier for the TiO layer to prevent it from direct contact with the corrosive medium; the TiO2 layer exhibits a high corrosion potential in acidic and alkaline environments, and is difficult to dissolve or react chemically; Ti 2+It has two unpaired d electrons, which can participate in charge transfer and conduction. The TiO layer is evenly distributed in the Ti4O7 crystal, and its continuity provides a quasi-two-dimensional electron transmission path. This geometric arrangement is conducive to reducing the scattering effect of electrons, thereby improving the conductivity.

[0147] The conductivity of the Ti4O7 carrier material prepared by the titanyl sulfate-polyethylene glycol reduction method is closely related to the phase purity of Ti4O7. After repeated experiments, the inventors determined the optimal reaction conditions: "First, the mass ratio of polyethylene glycol with an average relative molecular mass of 400 to titanium dioxide, a derivative of titanyl sulfate, must be 1:1, otherwise the phase purity of Ti4O7 will be reduced; second, the gel drying conditions need to be maintained at 150°C and 5h to balance the volatilization of sulfides and the particle size of nano-scale TiO2 precursors; too low a temperature will cause the sulfide to not be completely volatilized, and the subsequent reduction step cannot be carried out; too high a temperature will cause Ti The particle size of the O2 precursor is too large, which reduces the specific surface area of ​​the subsequent Ti4O7 carrier material; thirdly, the heat treatment conditions need to be maintained at 967°C and 3h. Too high or too low a heat treatment temperature will reduce the phase purity of Ti4O7, and too long a heat treatment time will reduce the specific surface area of ​​Ti4O7; the conductivity of the Ti4O7 carrier material prepared by the present invention was measured by a powder resistivity measurement system using a four-probe method at a compression pressure ranging from 3-64MPa, and the value was 1.2S / cm, which is very close to the classic carbon-based carrier XC-72R; high conductivity is one of the necessary conditions for a fuel cell catalyst carrier material.

[0148] The ethanol reduction method used is compatible with the preparation of Pt / Ti4O7 catalyst, IrO2 / Ti4O7 catalyst, Pt / W-SnO2 catalyst, and IrO2 / W-SnO2 catalyst. There is no need to change the equipment, and only minor adjustments need to be made to the process parameters.

[0149] The performance of the membrane electrodes prepared by the examples and comparative examples is described below.

[0150] Example 1

[0151] The catalyst [Pt / Ti4O7 (30%) and Pt / W-SnO2 (50%)], ionomer resin emulsion, isopropyl alcohol and ultrapure water are mixed in a certain proportion to prepare a slurry; wherein the ionomer resin emulsion contains 20% of dry resin;

[0152] The anode catalyst Pt / Ti4O7 corresponds to the anode slurry, and the cathode catalyst Pt / W-SnO2 corresponds to the cathode slurry; the proportions of each slurry are listed in Table 2; each slurry is a dispersion system, the catalyst and dry resin are dispersants, and the rest are dispersants;

[0153]

[0154] Table 2

[0155] After preparation, the anode slurry and cathode slurry are dispersed; each slurry uses the same dispersion equipment and process parameters; the entire slurry dispersion process is divided into three steps: pulping, grinding and ultrasound;

[0156] After dispersion, the anode spray slurry and cathode spray slurry are obtained respectively; then the particle size is detected by a laser nanoparticle size analyzer; if the particle size meets the technical requirements (D 50 ≤1μm, D 90 ≤2μm, D 99 ≤2.4μm), the next step of spraying can be carried out; if the particle size does not meet the technical requirements, the slurry must be re-dispersed;

[0157] After the slurry is dispersed, the CCM is prepared by a sprayer; after the CCM is sprayed, the membrane electrode is packaged with a gas diffusion layer and a PEN frame to obtain a membrane electrode A.

[0158] Example 2

[0159] The difference from Example 1 is that the cathode catalyst used in the cathode slurry is a Pt / C catalyst with a platinum content of 50%. The rest is the same as Example 1, and a membrane electrode B is obtained.

[0160] Example 3

[0161] The difference from Example 1 is that the anode slurry uses a Pt / C catalyst with a platinum content of 30% of the anode catalyst. The rest is the same as Example 1, and a membrane electrode C is obtained.

[0162] Comparative Example 1

[0163] The difference from Example 1 is that the anode slurry uses a Pt / C catalyst with a platinum content of 30% for the anode catalyst, and the cathode slurry uses a Pt / C catalyst with a platinum content of 50% for the cathode catalyst. The rest is the same as Example 1, and a membrane electrode D is obtained.

[0164] First, polarization curves of membrane electrodes A, B, C and D were characterized; the fuel was 99.999% pure hydrogen, 100% humidified hydrogen, and the stoichiometric ratio of hydrogen was 1.2; the oxidant was standard air prepared with high-purity nitrogen and high-purity oxygen, in which the oxygen content was 21%, the standard air was 100% humidified, and the stoichiometric ratio of standard air was 2.5; the battery temperature was 75°C; the outlet back pressure was 0.2Mpa gauge pressure; the results are shown in Figure 5As shown in the figure, the initial performance of membrane electrode D is the best, followed by membrane electrode B, and the performance of membrane electrode A and membrane electrode C is slightly lower. At each current density point, the maximum voltage difference between membrane electrode A and membrane electrode D is 13mV. This is because the commercial Pt / C catalyst uses the XC72R carrier, which has a good balance of specific surface area, conductivity and hydrophobicity. XC72R has a high specific surface area of ​​251m 2 / g, strong conductivity and suitable hydrophobicity.

[0165] The membrane electrodes A, B, C and D were respectively installed in the fixture of the single cell, 100% humidified nitrogen was introduced into the cathode side of the single cell fixture, and 100% humidified hydrogen was introduced into the anode side, the gas flow rate was 0.5 L / min, the gas inlet pressure was 50 kPa, the battery temperature was 80°C, the positive electrode of the electrochemical constant potential instrument was connected to the cathode side of the single fixture battery, and the negative electrode of the electrochemical constant potential instrument was connected to the anode side of the single cell fixture, the potentiostat potential was set between 0.6 V (3 s) and 1.0 V (3 s) for square wave cycling, the potential switching time was less than 0.5 s, and each cycle was 6 s; after a total of 10,000 cycles, the polarization curves A', B', C' and D' of the membrane electrodes A, B, C and D after 10,000 cycles were measured respectively; the results are shown as follows Figure 7 As shown;

[0166] from Figure 7 It can be seen that after 10,000 square wave cycles, the polarization curve A' of membrane electrode A has almost no potential decay at all current density points, and the polarization curve A' and polarization curve A almost do not overlap; while the polarization curves B', C' and D' all show different degrees of voltage decay compared with the polarization curves B, C and D (the smallest voltage decay amplitude is 20mV). Among them, the membrane electrode D, which uses commercial Pt / C catalyst for both cathode and anode, has the largest voltage decay amplitude, and the voltage decay at each current density point is high. Reach 50mV-67mV; this indicates that the anode carrier (Ti4O7) and the synthesized anode catalyst (30% Pt / Ti4O7), the selected cathode carrier (W-SnO2) and the synthesized cathode catalyst (50% Pt / W-SnO2) prepared by the present invention have very good durability; compared with the membrane electrode prepared by commercial Pt / C catalyst, although its initial polarization performance is slightly lower, its durability is very good, and after 10,000 square wave cycles, the electrical conductivity of the membrane electrode has almost no attenuation.

[0167] Example 4

[0168] The present invention mixes catalyst Pt / Ti4O7 (30%), IrO2 / Ti4O7 (20%), Pt / W-SnO2 (50%), IrO2 / W-SnO2 (20%), ionomer resin emulsion, isopropanol and ultrapure water in a certain proportion to prepare slurry; the ionomer resin contains 20% of dry resin;

[0169] Anode catalyst Pt / Ti4O7 is used as anode slurry, cathode catalyst Pt / W-SnO2 is used as cathode slurry, anode anti-reverse catalyst IrO2 / Ti4O7 is used as anode anti-reverse slurry, and cathode anti-reverse catalyst IrO2 / W-SnO2 is used as cathode anti-reverse slurry; the proportions of each slurry are prepared according to Table 1;

[0170] 5 parts of anode slurry and 1 part of anode anti-reverse slurry are mixed to obtain anode spray slurry A, and 20 parts of cathode slurry and 1 part of cathode anti-reverse slurry are mixed to obtain cathode spray slurry A; after the mixing is completed, the anode spray slurry A and the cathode spray slurry A are slurry dispersed; each slurry uses the same dispersion equipment and process parameters; the entire slurry dispersion step is divided into 3 steps: pulping, grinding and ultrasound;

[0171] Pulping is done by a pulping machine, which consists of a mechanical stirring blade, a rod-type ultrasonic crusher and a high-speed shearing machine; Figure 3 As shown, No. 1 is a mechanical stirring blade, No. 2 is a rod-type ultrasonic crusher, and No. 3 is a high-speed shearing machine; the temperature control function of the pulping machine is completed by a temperature sensor and a water cooling unit; the speed of the mechanical stirring blade is set to 40r / min, the power of the rod-type ultrasonic crusher is set to 800W, the frequency is set to 20kHz, the speed of the high-speed shearing machine is set to 18000r / min, the temperature of the coolant of the water cooling unit is set to 15℃±1℃, and the pulping time is set to 20min;

[0172] Grinding is done by a grinding machine, which consists of grinding rods and grinding beads; Figure 4 As shown, serial number 4 is the tank body, serial number 5 is the grinding rod, serial number 6 is the grinding bead, and serial number 7 is the interlayer of the tank wall; the temperature control function of the grinder is completed by the temperature sensor and the water cooling unit, and the coolant flows through the interlayer of the tank wall to cool the slurry; the rotation speed of the grinding rod is set to 3.1m / s, zirconium dioxide grinding beads with φ=0.03mm are selected, the temperature of the coolant of the water cooling unit is set to 15℃±1℃, and the slurry making time is set to 20min.

[0173] The ultrasonic cleaning machine is used for ultrasonic cleaning. The temperature control function of the ultrasonic cleaning machine is completed by a temperature sensor and a water cooling unit. The ultrasonic power is set to 750W, the temperature of the coolant of the water cooling unit is controlled to 15℃±1℃, and the ultrasonic time is set to 20min.

[0174] After dispersion, the anode spray slurry A and the cathode spray slurry A are obtained respectively; then the particle size is detected by a laser nanoparticle size analyzer; if the particle size meets the technical requirements (D 50 ≤1μm, D 90 ≤2μm, D 99 ≤2.4μm), the next step of spraying can be carried out; if the particle size does not meet the technical requirements, the slurry must be re-dispersed;

[0175] After the slurry dispersion of the anode spray slurry A and the cathode spray slurry A is completed, the CCM is prepared by a sprayer; after the CCM spraying is completed, the membrane electrode is packaged with a gas diffusion layer and a PEN frame to obtain a membrane electrode E.

[0176] Comparative Example 2

[0177] Different from Example 4, the cathode spraying slurry A only contains cathode slurry but does not contain cathode anti-reverse electrode slurry. The rest is the same as Example 4, and a membrane electrode F is obtained.

[0178] Comparative Example 3

[0179] The difference from Example 4 is that the anode spraying slurry A contains only anode slurry but no anode anti-reverse slurry. The rest is the same as Example 4, and a membrane electrode G is obtained.

[0180] First, polarization curves of membrane electrodes E, F and G were characterized; the fuel was 99.999% pure hydrogen, 1.2 stoichiometric ratio, 100% humidification; the oxidant was standard air prepared by high-purity nitrogen and high-purity oxygen, in which the oxygen content was 21%, the standard air 2.5 stoichiometric ratio, 100% humidification; the cell temperature was 75°C; the outlet back pressure was 0.2Mpa gauge pressure; the results are shown in Figure 6 As shown, the initial polarization curves of membrane electrodes E, F, and G are very close;

[0181] The membrane electrodes E, F and G were respectively installed in the fixture of the single cell. The test simulated the anode completely under-gassing condition, that is, nitrogen was introduced into the anode and air was introduced into the cathode. The gas pressure was normal pressure, the gas flow rate was 1L / min, 100% humidification, the battery temperature was 75°C, the single cell was connected to a constant current source, the anode of the single cell was connected to the positive electrode of the constant current source, the cathode of the single cell was connected to the negative electrode of the constant current source, and the current density was set to 0.2A / cm 2 , set the battery cut-off voltage to -1.5V;

[0182] Regarding the shutdown reverse continuous operation time of the anode completely lacking gas, the single cell anode is first supplied with hydrogen, with a flow rate of 1L / min, normal pressure, 100% humidification, and an external constant current source is connected to simulate the anode completely lacking gas working condition, and the current density is set to 0.2A / cm 2After the voltage of the single cell is stable, the anode is switched from hydrogen to nitrogen to simulate the anode completely under-gassing condition; when simulating the anti-reverse polarity condition of the anode completely under-gassing, the voltage of the membrane electrodes E, F and G drops rapidly to below 0V; if the voltage of the membrane electrode reaches the cut-off voltage of -1.5V, the constant current source will automatically cut off the current, and the anti-reverse polarity test ends; if the membrane electrode voltage is always between -1.5V and 0V and continues to run for 90 minutes when simulating the anti-reverse polarity condition of the anode completely under-gassing, the constant current source will automatically cut off the current, and the anti-reverse polarity test of the anode completely under-gassing condition ends;

[0183] After the anti-reverse polarity test of the anode completely under-gassing condition is completed, the membrane electrodes E, F and G are reactivated and the polarization curves E', F' and G' of the membrane electrodes E, F and G under the simulated anode completely under-gassing condition are recorded, and the voltage attenuation values ​​of the polarization curves E', F' and G' relative to the polarization curves E, F and G are recorded;

[0184] Since the anode of the membrane electrode F does not have a Pt / Ti4O7 catalyst, under the condition of simulating a complete anode gas shortage, the voltage of the membrane electrode F drops to the cut-off voltage of -1.5V within a running time of less than 1min. After the membrane electrode F was disassembled, it was found that its proton exchange membrane was broken down; this indicates that the membrane electrode F does not have the function of resisting complete anode gas shortage;

[0185] The anti-reverse polarity test results of membrane electrode E and membrane electrode G under the condition of complete anode under-gassing are as follows: Figure 8 shown; from Figure 8 It can be seen that after the membrane electrode E and membrane electrode G experienced the anode complete gas shortage anti-reverse polarity test, their polarization curves E' and G' both showed a small attenuation, the average voltage attenuation of the membrane electrode E was 12mV, the average voltage attenuation of the membrane electrode G was 15mV, and the rated power loss was less than 4%; this shows that the membrane electrode E and the membrane electrode G both have the function of resisting the complete anode gas shortage;

[0186] Since the anti-reverse polarity test is a destructive test, membrane electrodes E, F and G are re-prepared according to Example 4, Comparative Example 2 and Comparative Example 3 to simulate the anti-reverse polarity working condition test of the anode part being short of gas;

[0187] Regarding the shutdown reverse continuous operation time of the anode partial gas shortage, hydrogen is first passed through the anode of the single cell, with a flow rate of 1L / min, normal pressure, 100% humidification, and an external constant current source is connected to simulate the anode partial gas shortage working condition, and the current density is set to 0.5A / cm 2After the voltage of the single cell is stable, the anode is switched from hydrogen to a mixed gas (95% nitrogen + 5% oxygen) to simulate the anode partial gas shortage condition; when simulating the anti-reverse polarity condition of partial gas shortage of the anode, the voltage of the membrane electrodes E, F and G drops rapidly to below 0V; if the voltage of the membrane electrode reaches the cut-off voltage of -1.5V, the constant current source automatically cuts off the current, and the anti-reverse polarity test ends; if the membrane electrode voltage is always between -1.5V and 0V and continues to run for 90 minutes when simulating the anti-reverse polarity condition of partial gas shortage of the anode, the constant current source automatically cuts off the current, and the anti-reverse polarity test of the anode partial gas shortage condition ends;

[0188] After the anti-reverse polarity test of the anode partial gas shortage condition is completed, the membrane electrodes E, F and G are reactivated and the polarization curves E', F' and G' of the membrane electrodes E, F and G under the simulated anode complete gas shortage condition are recorded, and the voltage attenuation values ​​of the polarization curves E', F' and G' relative to the polarization curves E, F and G are recorded;

[0189] Since the cathode of the membrane electrode G does not have an IrO2 / W-SnO2 catalyst, when the anode is partially short of gas, the voltage of the membrane electrode G drops to a cut-off voltage of -1.5V within a running time of less than 3 minutes. After the membrane electrode G is disassembled, it is found that its proton exchange membrane is broken down; this indicates that the membrane electrode G does not have the function of resisting the anode partial short of gas;

[0190] The anti-reverse polarity test results of membrane electrode E and membrane electrode F under the condition of partial gas shortage in the anode are as follows: Fig. 9 shown; from Fig. 9 It can be seen that after the membrane electrode E and membrane electrode F experienced the anode partial gas shortage anti-reverse polarity test, their polarization curves E' and F' both showed a small attenuation, the average voltage attenuation of the membrane electrode E was 13mV, the average voltage attenuation of the membrane electrode F was 14mV, and the rated power loss was less than 4%; this shows that the membrane electrode E and the membrane electrode F both have the function of resisting the anode partial gas shortage;

[0191] comprehensive Figure 8 and Fig. 9 The polarization curve data before and after anode reversal (complete anode under-gassing and partial anode under-gassing) indicate that the membrane electrode E prepared by the present invention has the dual function of resisting complete anode under-gassing and partial anode under-gassing.

[0192] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0193] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A catalyst coated membrane, comprising a proton exchange membrane, an anode catalyst layer, and a cathode catalyst layer, wherein one surface of the proton exchange membrane is coated with the anode catalyst layer, and the other surface of the proton exchange membrane is coated with the cathode catalyst layer, the anode catalyst layer is obtained by spraying an anode spray slurry on one surface of the proton exchange membrane, and the cathode catalyst layer is obtained by spraying a cathode spray slurry on the other surface of the proton exchange membrane, characterized in that: The anode spraying slurry is composed of a mixture of an anode slurry and an anode anti-reverse slurry, the anode slurry is composed of a dispersant and a dispersoid, the dispersant of the anode slurry is ultrapure water and isopropanol, the dispersoid of the anode slurry is a dry resin and an anode catalyst Pt / Ti4O7, and the solid content of the anode slurry after mixing is 1% to 2%; the anode anti-reverse slurry is composed of a dispersant and a dispersoid, the dispersant of the anode anti-reverse slurry is ultrapure water and isopropanol, the dispersoid of the anode anti-reverse slurry is a dry resin and an anode anti-reverse catalyst IrO2 / Ti4O7, and the solid content of the anode anti-reverse slurry after mixing is 1% to 2%; The cathode spraying slurry consists of cathode slurry and cathode anti-reverse pole slurry. The cathode slurry consists of a dispersant and a dispersant. The dispersant of the cathode slurry is ultrapure water and isopropyl alcohol. The dispersant of the cathode slurry is a dry resin and a cathode catalyst Pt / W-SnO2. After mixing, the solid content of the cathode slurry is 1% to 2%. The cathode anti-reverse pole slurry consists of a dispersant and a dispersant. The dispersant of the cathode anti-reverse pole slurry is ultrapure water and isopropyl alcohol. The dispersant of the cathode anti-reverse pole slurry is a dry resin and a cathode anti-reverse pole catalyst IrO2 / W-SnO2. After mixing, the solid content of the cathode anti-reverse pole slurry is 1% to 2%.

2. A catalyst coated membrane according to claim 1, characterized in that: The volume ratio of ultrapure water to isopropanol in the anode slurry is 1:1-4, and the mass ratio of dry resin to Pt / Ti4O7 is 21:50; The volume ratio of ultrapure water and isopropanol in the anode anti-reverse slurry is 1:1-4, and the mass ratio of dry resin and IrO2 / Ti4O7 is 12:25; The volume ratio of ultrapure water to isopropanol in the cathode slurry is 1:1-4, and the mass ratio of dry resin to Pt / W-SnO2 is 3:10; The volume ratio of ultrapure water to isopropanol in the cathode anti-reverse electrode slurry is 1:1-4, and the mass ratio of dry resin to IrO2 / W-SnO2 is 12:

25.

3. A catalyst coated membrane according to claim 2, characterized in that: Mixing 5 parts of anode slurry with 1 part of anode anti-reverse slurry to obtain anode spray slurry; mixing 20 parts of cathode slurry with 1 part of cathode anti-reverse slurry to obtain cathode spray slurry, and after the mixing is completed, slurry dispersion is performed on the anode spray slurry and the cathode spray slurry, and the slurry dispersion steps include pulping, grinding and ultrasound; After the slurry dispersion of the anode spray slurry and the cathode spray slurry is completed, the preparation of the CCM is completed by the spraying machine.

4. A method for preparing a catalyst coated membrane, which is used to prepare the catalyst coated membrane according to any one of claims 1 to 3, characterized in that: It includes the following steps: S1, preparing Ti4O7, thereby obtaining anode catalyst Pt / Ti4O7 and anode anti-reverse catalyst IrO2 / Ti4O7; S2, obtaining cathode catalyst Pt / W-SnO2 and cathode anti-reversal catalyst IrO2 / W-SnO2 through W-SnO2; S3, preparing anode slurry, cathode slurry, anode anti-reverse slurry, cathode anti-reverse slurry; S4, 5 parts of anode slurry and 1 part of anode anti-reverse slurry are mixed to obtain anode spray slurry, and 20 parts of cathode slurry and 1 part of cathode anti-reverse slurry are mixed to obtain cathode spray slurry; after the mixing is completed, the anode spray slurry and the cathode spray slurry are slurry dispersed; the dispersion steps of the anode spray slurry and the cathode spray slurry both include pulping, grinding and ultrasound; S5. After the anode spraying slurry and the cathode spraying slurry are dispersed, the catalyst coating membrane is prepared by a spraying machine.

5. The method for preparing a catalyst coating membrane according to claim 4, characterized in that: In step S1, after the preparation of Ti4O7 is completed, the anode catalyst Pt / Ti4O7 and the anode anti-reverse catalyst IrO2 / Ti4O7 need to be prepared through Ti4O7; The preparation of the anode catalyst Pt / Ti4O7 includes the following steps: S12, add diammine dinitrite platinum Pt(NO2)2(NH3)2 and 0.7 g of Ti4O7 carrier to 200 ml of distilled water, disperse for 1 hour by magnetic stirring, and adjust the amount of platinum precursor added so that the mass fraction of Pt in the final catalyst reaches 30%; stir to evenly suspend the Ti4O7 particles to increase the surface area to facilitate the platinum ion (Pt 2+ ) adsorption; Add 30 ml of ethanol and continue stirring at room temperature for 30 minutes; ethanol, as an auxiliary agent, changes the surface tension of the system, promotes the uniform adsorption of platinum ions on the surface of the carrier material Ti4O7, reduces the agglomeration of particles, and makes the catalyst precursor form a more uniform dispersion state; The temperature was raised to 95°C and stirred for 12 hours to obtain a Pt / Ti4O7 catalyst. In this process, ethanol was mainly used as a reducing agent to convert platinum ions (Pt 2+ ) is reduced to platinum (Pt 0 ) nanoparticles; at the same time, ethanol as a solvent helps to stabilize the dispersion of the precursor and prevent the aggregation of particles; The Pt / Ti4O7 catalyst was separated from the solution by vacuum filtration, washed with 1L of distilled water, and dried at room temperature for 12 hours; unreacted precursors, ethanol and other soluble impurities were removed by washing to ensure the purity of the catalyst; water was evaporated by drying at room temperature to form a preliminary solid structure, providing a stable foundation for subsequent heat treatment; The Pt / Ti4O7 catalyst was dried at 80°C for 10 hours in a nitrogen atmosphere; and dried at 200°C for 2 hours in a helium atmosphere. Low-temperature drying in a nitrogen environment was performed to remove physically adsorbed water or organic solvent residues remaining in the material. The temperature was raised to 200°C in a helium environment to improve the distribution uniformity and binding force of platinum nanoparticles on the Ti4O7 carrier and optimize the structure of the Pt / Ti4O7 catalyst. The inert environment of helium was used to avoid oxidation or further reduction of the particles and maintain the stability and activity of the Pt / Ti4O7 catalyst.

6. The method for preparing a catalyst coating membrane according to claim 5, characterized in that: The preparation of the anode anti-reverse polarity catalyst IrO2 / Ti4O7 comprises the following steps: S13, adding iridium chloride H2IrCl6 and 0.8 g of Ti4O7 carrier to 200 ml of distilled water, and dispersing them by magnetic stirring for 1 hour, while adjusting the amount of iridium precursor added so that the mass fraction of IrO2 in the final catalyst reaches 20%; stirring to uniformly suspend the Ti4O7 particles to increase the surface area to facilitate the iridium ion (Ir 4+ ) adsorption; Add 50 ml of ethanol and continue stirring at room temperature for 60 minutes; ethanol, as an auxiliary agent, changes the surface tension of the system, promotes the uniform adsorption of iridium ions on the surface of the carrier material Ti4O7, reduces the agglomeration of particles, and makes the catalyst precursor form a more uniform dispersion state; The temperature was raised to 90°C and stirred for 16 hours to obtain Ir / Ti4O7. Ethanol was mainly used as a reducing agent in this process to convert iridium ions (Ir 4+ ) is reduced to iridium (Ir 0 ) nanoparticles; at the same time, ethanol as a solvent helps to stabilize the dispersion of the precursor and prevent the aggregation of particles; Ir / Ti4O7 was separated from the solution by vacuum filtration, washed with 1L of distilled water, and dried at room temperature for 12 hours; unreacted precursors, ethanol and other soluble impurities were removed by washing to ensure the purity of the material; water was evaporated by drying at room temperature to form a preliminary solid structure, providing a stable foundation for subsequent heat treatment; The Ir / Ti4O7 material was dried at 80°C for 10 hours in a nitrogen atmosphere; the material was dried at low temperature in a nitrogen environment to remove the physically adsorbed water or organic solvent residues remaining in the material; In a nitrogen / oxygen mixed atmosphere, the volume fraction ratio is φ(nitrogen):φ(oxygen)=95%:5%; and the Ir / Ti4O7 material is dried and oxidized at 200°C for 2 hours to obtain an IrO2 / Ti4O7 catalyst; oxidation and drying in a mixed atmosphere are performed, on the one hand, to form iridium dioxide nanoparticles (IrO2); on the other hand, to improve the distribution uniformity and binding force of the iridium dioxide nanoparticles on the Ti4O7 carrier.

7. The method for preparing a catalyst coating membrane according to claim 4, characterized in that: Step S2 includes preparing cathode catalyst Pt / W-SnO2 and cathode anti-reversal catalyst IrO2 / W-SnO2 by W-SnO2; The preparation of cathode catalyst Pt / W-SnO2 includes the following steps: Platinum diamine dinitrite Pt(NO2)2(NH3)2 and 0.5 g of W-SnO2 carrier were added to 200 ml of distilled water and dispersed by magnetic stirring for 1 hour. At the same time, the amount of platinum precursor added was adjusted to make the mass fraction of Pt in the final catalyst reach 50%; the W-SnO2 particles were evenly suspended by stirring to increase the surface area to facilitate the platinum ion (Pt 2+ ) adsorption; Add 50 ml of ethanol and continue stirring at room temperature for 60 minutes; ethanol, as an auxiliary agent, changes the surface tension of the system, promotes the uniform adsorption of platinum ions on the surface of the carrier material W-SnO2, reduces the agglomeration of particles, and makes the catalyst precursor form a more uniform dispersion state; The temperature was raised to 90°C and stirred for 16 hours to obtain a Pt / W-SnO2 catalyst. Ethanol was mainly used as a reducing agent in this process to convert platinum ions (Pt 2+ ) is reduced to platinum (Pt 0 ) nanoparticles; at the same time, ethanol as a solvent helps to stabilize the dispersion of the precursor and prevent the aggregation of particles; The Pt / W-SnO2 catalyst was separated from the solution by vacuum filtration, washed with 1L of distilled water, and dried at room temperature for 12 hours; unreacted precursors, ethanol, and other soluble impurities were removed by washing to ensure the purity of the catalyst; water was evaporated by drying at room temperature to form a preliminary solid structure, providing a stable foundation for subsequent heat treatment; The Pt / W-SnO2 catalyst was dried at 80°C for 10 hours in a nitrogen atmosphere; the catalyst was dried at low temperature in a nitrogen environment to remove the physically adsorbed water or organic solvent residues remaining in the material; In a helium atmosphere, the Pt / W-SnO2 catalyst was dried at 200°C for 2 hours. The temperature was raised to 200°C in the helium environment to improve the distribution uniformity and binding force of the platinum nanoparticles on the W-SnO2 carrier and optimize the structure of the Pt / W-SnO2 catalyst. The inert environment of helium prevented oxidation or further reduction of the particles, thereby maintaining the stability and activity of the Pt / W-SnO2 catalyst.

8. The method for preparing a catalyst coating membrane according to claim 7, characterized in that: The preparation of the cathode anti-reversal catalyst IrO2 / W-SnO2 comprises the following steps: Chloroiridic acid H2IrCl6 and 0.8 g of Ti4O7 carrier were added to 200 ml of distilled water and dispersed by magnetic stirring for 1 hour. At the same time, the amount of iridium precursor added was adjusted to make the mass fraction of IrO2 in the final catalyst reach 20%; Ti4O7 particles were evenly suspended by stirring to increase the surface area to facilitate the iridium ion (Ir 4+ ) adsorption; Add 50 ml of ethanol and continue stirring at room temperature for 60 minutes; ethanol, as an auxiliary agent, changes the surface tension of the system, promotes the uniform adsorption of iridium ions on the surface of the carrier material Ti4O7, reduces the agglomeration of particles, and makes the catalyst precursor form a more uniform dispersion state; The temperature was raised to 90°C and stirred for 16 hours to obtain Ir / Ti4O7. Ethanol was mainly used as a reducing agent in this process to convert iridium ions (Ir 4+ ) is reduced to iridium (Ir 0 ) nanoparticles; at the same time, ethanol as a solvent helps to stabilize the dispersion of the precursor and prevent the aggregation of particles; Ir / Ti4O7 was separated from the solution by vacuum filtration, washed with 1L of distilled water, and dried at room temperature for 12 hours; unreacted precursors, ethanol and other soluble impurities were removed by washing to ensure the purity of the material; water was evaporated by drying at room temperature to form a preliminary solid structure, providing a stable foundation for subsequent heat treatment; The Ir / Ti4O7 material was dried at 80°C for 10 hours in a nitrogen atmosphere; the material was dried at low temperature in a nitrogen environment to remove the physically adsorbed water or organic solvent residues remaining in the material; In a nitrogen / oxygen mixed atmosphere, the volume fraction ratio is φ(nitrogen):φ(oxygen)=95%:5%; and the Ir / Ti4O7 material is dried and oxidized at 200°C for 2 hours to obtain an IrO2 / Ti4O7 catalyst; oxidation and drying in a mixed atmosphere are performed, on the one hand, to form iridium dioxide nanoparticles (IrO2); on the other hand, to improve the distribution uniformity and binding force of the iridium dioxide nanoparticles on the Ti4O7 carrier.

9. The method for preparing a catalyst coated membrane according to claim 4, characterized in that: In step S3, four slurries including anode slurry, cathode slurry, anode anti-reverse slurry and cathode anti-reverse slurry are mixed and obtained; Step S31, mixing and obtaining anode slurry, wherein the volume ratio of ultrapure water and isopropanol in the anode slurry is 1:1-4, the mass ratio of dry resin and Pt / Ti4O7 is 21:50, and the solid content in the anode slurry after mixing is 1%-2%; Step S32, mixing and obtaining cathode slurry, wherein the volume ratio of ultrapure water and isopropanol in the cathode slurry is 1:1-4, the mass ratio of dry resin and Pt / W-SnO2 is 3:10, and the solid content in the cathode slurry after mixing is 1%-2%; Step S33, mixing and obtaining anode anti-reverse electrode slurry, wherein the volume ratio of ultrapure water and isopropanol in the anode anti-reverse electrode slurry is 1:1-4, the mass ratio of dry resin and IrO2 / Ti4O7 is 12:25, and the solid content in the anode anti-reverse electrode slurry after mixing is 1%-2%; Step S34, cathode anti-reverse electrode slurry is obtained by mixing, wherein the volume ratio of ultrapure water and isopropyl alcohol in the cathode anti-reverse electrode slurry is 1:1-4, the mass ratio of dry resin and IrO2 / W-SnO2 is 12:25, and the solid content in the cathode anti-reverse electrode slurry after mixing is 1%-2%.

10. A method for preparing Ti4O7, which is used for preparing Ti4O7 used in a method for preparing a catalyst coating membrane as claimed in any one of claims 4 to 9, characterized in that: The Ti4O7 carrier material is prepared by a titanyl sulfate-polyethylene glycol reduction method, which comprises the following steps: A beaker is placed in a fume hood, and a mixed solvent is added to the beaker, wherein the mixed solvent consists of deionized water and polyethylene glycol, wherein the molecular weight range of the polyethylene glycol is 360-440 and the average molecular weight is 400, and solid titanium oxysulfate (TiOSO4) is weighed and dissolved in the beaker, so that the titanium oxysulfate is dispersed at room temperature, and the derivative of titanium oxysulfate (TiOSO4) decomposed at room temperature includes titanium dioxide, so that the mass ratio of polyethylene glycol to titanium dioxide in the mixed solvent is 1:1; at room temperature, the initial state of the dispersion is white; An aluminum bathtub is placed in a fume hood, and a beaker containing titanyl sulfate and a mixed solvent is placed in the bathtub; aluminum beads are added to the bathtub as a heat-conducting medium, magnetic stirring is started, and the system is heated and maintained at a heating temperature while stirring continuously; during the heating process, the white dispersion gradually turns into a yellow solution until the solution further turns into a brown gel; The magnetic stirring was continued, and the heating temperature of the aluminum bathtub was further increased to 150°C and maintained at this temperature for 5 h. During the heating period, the brown gel gradually transformed into a black powder. After the black powder in the beaker has cooled to room temperature, it is fully ground using an agate mortar, and the ground powder is transferred to an alumina boat and sealed in a quartz tube; The sealed quartz tube was taken out from the fume hood and placed in a tube furnace. Before heating in the tube furnace, the quartz tube was purged with N2 to exhaust the residual air in the tube. Then the gas flow was switched and a H2 / Ar mixed gas was introduced. The sample was heated from room temperature to 967°C at a heating rate of 10°C / min and maintained at this temperature for 3h to obtain Ti4O7.